2017
DOI: 10.1080/02699052.2017.1363409
|View full text |Cite
|
Sign up to set email alerts
|

A pilot treatment study for mild traumatic brain injury: Neuroimaging changes detected by MEG after low-intensity pulse-based transcranial electrical stimulation

Abstract: The present study demonstrates, for the first time, the neuroimaging-based documentation of the effect of LIP-tES treatment on brain functioning in mTBI. The mechanisms of LIP-tES treatment are discussed, with an emphasis on LIP-tES's potentiation of the mTBI healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Since this is an emerging area of research, limited studies met the inclusion criteria for review. Additionally, of the 14 studies included, only six were rated as having a low risk of bias (Leung et al, 2016b(Leung et al, , 2018Wilke et al, 2017;Choi et al, 2018;Moussavi et al, 2019;Stilling et al, 2019b), and the other eight studies had several methodological limitations (Walker et al, 2002;Fitzgerald et al, 2011;Koski et al, 2015;Leung et al, 2016a;Huang et al, 2017;Paxman et al, 2018;Ansado et al, 2019;Stilling et al, 2019a). At face value, all but one of the studies demonstrated that neuromodulation had a positive effect on the various symptoms measured and sometimes neurophysiological functioning following mTBI, as detailed in Supplementary Table 6B.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since this is an emerging area of research, limited studies met the inclusion criteria for review. Additionally, of the 14 studies included, only six were rated as having a low risk of bias (Leung et al, 2016b(Leung et al, , 2018Wilke et al, 2017;Choi et al, 2018;Moussavi et al, 2019;Stilling et al, 2019b), and the other eight studies had several methodological limitations (Walker et al, 2002;Fitzgerald et al, 2011;Koski et al, 2015;Leung et al, 2016a;Huang et al, 2017;Paxman et al, 2018;Ansado et al, 2019;Stilling et al, 2019a). At face value, all but one of the studies demonstrated that neuromodulation had a positive effect on the various symptoms measured and sometimes neurophysiological functioning following mTBI, as detailed in Supplementary Table 6B.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofeedback was effective for reducing excessive delta wave EEG activity (Huang et al, 2017) as well as post-concussion symptom scores (Walker et al, 2002;Huang et al, 2017) and sleep disturbance (Huang et al, 2017). Improved rates of return to work were also seen with both rTMS and neurofeedback (Walker et al, 2002;Stilling et al, 2019b).…”
Section: Risk Of Bias and Quality Of Evidencementioning
confidence: 94%
See 2 more Smart Citations
“…Previous clinical studies have reported that electrical stimulation (ES) can be used to treat TBI, and its complications effectively. [1719] However, no systematic review has explored the effect and safety of ES for the treatment of children with limbs spasticity (LS) after traumatic brain injury (TBI). Thus, this systematic review will aim to assess the effect and safety of ES for the treatment of LS following TBI among children population.…”
Section: Introductionmentioning
confidence: 99%